A Climatology of Narrow Cold‐Frontal Rainbands in Southern California. Issue 2 (12th January 2022) - de Orla‐Barile, Marian; Cannon, Forest; Oakley, Nina S.; Ralph, F. Martin
Abstract: Narrow cold‐frontal rainbands (NCFRs) produce short‐duration, high‐intensity precipitation associated with flash flooding and debris flows in Southern California, including the extremely destructive 2018 Montecito event. This manuscript presents the first known catalog of NCFR events in this region during winter seasons 1995–2020. A manual approach was used to identify NCFRs in radar imagery, supported by rain gauges and atmospheric reanalysis products. In total, 94 NCFRs were observed, with an average of three landfalling events occurring per water year. Propagation and impacts of these NCFRs were also investigated. Composite analyses of synoptic conditions reveal similarities across events; however, individual NCFRs exist on a spectrum of atmospheric conditions, precipitation intensity, and associated hazards. This regional record serves as a control dataset for the development of an objective identification algorithm and supports the evaluation and improvement of forecasting procedures. Methods established here are transferrable to other mid‐latitude regions with limited radar coverage. Plain Language Summary: Narrow cold‐frontal rainbands produce short‐duration (<1‐hr), high‐intensity precipitation associated with flash floods and debris flows in Southern California, including the extremely destructive 2018 Montecito event. Prior research describes development, predictability, and associated hazards of these bands, though no known long‐term record of their occurrence and climatological characteristics exists within the United States. This study provides the first known catalog of narrow cold‐frontal rainbands during the winter seasons of 1995–2020 in Southern California, and explores characteristics of these features such as frequency, movement, and the large‐scale meteorology that drives them. Events were documented manually using rain gauge observations, radar data, and output from atmospheric models. In total, 94 rainbands were documented during the study period, with an average of three landfalling events occurring in Southern California per water year. The intensity and impacts across the recorded events varied, though common weather patterns, including strengthening cyclones near the California coast, were associated with the documented events. This catalog supports weather forecasting efforts as well as the future development of an automated detection algorithm. Key Points: Southern California experienced 94 narrow cold‐frontal rainbands over 26 water years from 1995 to 2020 Common synoptic conditions associated with narrow cold‐frontal rainband development include a deepening cyclone off of the California coast Future work can focus on the development of automated detection algorithms for NCFR identification using radar, and improved forecasting